Juvenile tree dynamics in changing landscapes: effects of overstory-mediated microclimates on dryland tree recruitment vary across climatic gradients - Hill, Edward M., author; Redmond, Miranda D., advisor; Ocheltree, Troy W., advisor; Bradford, John B., committee member; Smith, Melinda D., committee member (Colorado State University. Libraries, 2024)
Climate change impacts the future viability of plant species and communities directly through effects on demographic processes and indirectly through structural dynamics. Regeneration, establishment, growth, and survival of juvenile trees can be especially vulnerable processes in forest and woodland community development because juvenile trees are typically not able to tolerate abiotic stress as effectively as more mature trees. Because of this elevated sensitivity to climate-related stressors, juvenile establishment patterns are fundamental to understanding long-term species persistence. Overstory tree structure is an important mediating influence of the impacts of climate change in forest and woodland communities, particularly through influences on resource availability. Fine-scale variation in overstory tree size, density, and species influence primary plant resource requirements, including light availability, atmospheric heat and moisture, precipitation throughfall and soil water availability, and soil nutrient availability. Juvenile trees of different species can benefit from buffering of microclimate conditions by overstory trees, like direct radiation and extreme temperature variation, and experience competitive interactions for light and soil resources, especially in resource-limited communities. Yet, juvenile trees can span a range of sizes and physical maturity and vary in their capacity to acquire resources or tolerate resource limitations, and therefore can differ in facilitative versus competitive relationships with overstory conditions. Amplifying the complexity of these relationships, interannual variation in weather conditions, such as drier or wetter years than normal, influences the degree to which juvenile trees experience facilitative or competitive relationships with overstory trees. Indeed, the extent of microclimate effects on regeneration processes depend in part on the complex covariance of air temperature and humidity (thus, vapor pressure deficit), moisture availability (precipitation and soil moisture), and photosynthetically active radiation (i.e., light). In the absence of temperature and moisture limitations, trees may benefit from additional light availability for photosynthesis; alternatively, if temperature or moisture conditions are limiting, juveniles may benefit more from buffering influences of overstory, at the expense of decreased light availability. For dry forests and woodlands of the western U.S. which are at the forefront of climate change-driven tree recruitment vulnerabilities, greater resolution into juvenile relationships with overstory structure, and microclimate buffering, will substantially enhance the ability to evaluate and predict the effects of increasingly marginal climate space on their persistence. In this dissertation, I evaluated juvenile tree regeneration, growth, and survival in dryland forest and woodland systems relative to the mediating influences of overstory trees, across ranges of juvenile sizes, interannual weather variation, and broad climatic and elevational environmental gradients. In Chapter 1, I investigated survival and growth of ponderosa pine and Douglas-fir newly germinated seedlings, and older, larger seedlings to variation in overstory structure and associated microclimate conditions at fine-spatial scales. This study showed that while newly germinated seedlings were more sensitive to interannual variation in microclimates, overall survival and growth of younger and older seedlings were highest in microclimates with above-average warm and dry air during early-growing season months, and above-average light conditions. Importantly, the structural and microclimate influences on survival and growth over three years of study were primarily associated with the first year of study during which spring weather was abnormally cool and more humid. These results illustrated the environmental context for the initiation of survival and growth trajectories observed in this study, and demonstrate both spatially and temporally narrow conditions in which survival and growth was collectively greatest for both species. In Chapters 2 and 3, I investigated physiological and growth differences of juvenile piñon pine in dead and live overstory microenvironments over two years following experimentally-induced mortality of overstory trees. In Chapter 2, I measured photosynthetic and stomatal conductance rates of juveniles from among the smallest to largest individuals present in a middle-elevation piñon-juniper site in the core of the geographic distribution of two-needle piñon pine. Larger juveniles in dead overstory environments showed the highest photosynthetic and stomatal conductance rates. However, juveniles of all sizes were overall similarly limited by lower soil moisture and hot and dry microclimate conditions in both live and dead overstory environments. Given these limitations, the results of this study demonstrate the susceptibility of all juvenile piñon trees to hot and dry microclimates, which can be exacerbated both by mortality of overstory trees and by projections of future hotter and drier climate in these woodlands. In Chapter 3, I measured branch growth of juvenile piñon trees at six different sites spanning a gradient of latitudinal climate differences from hotter and drier southern locations to cooler and dry northern locations, and local elevation gradients from low to mid to high elevation piñon-juniper woodlands. Growth in post-overstory mortality years relative to mean growth prior to overstory mortality ("growth ratios") of juveniles across sizes was consistently higher in dead compared to live overstory environments only for middle- and high-elevation sites in our mid-latitude study region of southwestern Colorado, which had cooler and wetter post-overstory mortality weather conditions compared to other regions. Moreover, differences among sites were likely also related to typical climate differences associated both with latitude, where drier sites at southern and northern latitudes showed little growth responses to overstory mortality, and associated with elevation, where growth ratios were highest at the highest elevation site which has more moderate temperature and precipitation conditions on average. The results of this dissertation provide evidence for microclimate and juvenile tree survival outcomes in a dry forest restoration treatment and show the impact of acute structural change following overstory tree die-off on physiological and growth activity of juvenile piñon pine. The findings presented here provide ecologists and land managers with new information on the nuances of spatially and temporally narrow regeneration niches of species in dry mixed-conifer forests, and potential patterns and mechanisms of juvenile piñon pine resilience – but also potential future sensitivity – following overstory mortality. Importantly, results of these studies emphasize the role of interannual variation in weather conditions in driving specific forest and woodland development trajectories.
Keywords: microclimate; overstory structure; tree regeneration; ontogeny; dryland; population